Infectious Complications in Severely Burned Adult Patients-Diagnostic and Therapeutic Algorithm - Andreea GROSU-BULARDA; Andra-Luana LAZARESCU; Mihaela-Cristina ANDREI; Dan Aurel IONESCU; Adrian FRUNZA; Sabina GRAMA; Alexandru STOIAN; Florin Vlad HODEA; Tiberiu Paul NEAGU; Serban ARGHIR POPESCU; Ioan LASCAR (Modern Medicine)
Severe burn injuries represent a major challenge to the entire healthcare system in developing countries and even for states with a high standard of care. A clear understanding of the physiopathology of burn injuries is essential for providing an adequate prompt treatment to ensure an optimal patient outcome. Early recognition and treatment of burns complications, especially severe infections represent an important prevention strategy, improving survival after these severe injuries. Specific treatment must be conducted according to the characteristics of the patients in order to reduce morbidity and mortality and avoid the development of antimicrobial resistance. A diagnostic and therapeutic algorithm is presented, centered on infectious source prevention and control with early surgical excision and skin grafting together with culture-guided antimicrobial therapy. It is a known fact that, indifferent of the involved germ, the best intervention for both prophylaxis and treatment of infections in the burn patient is the early excision of the devitalized tissue and subsequent closure of burn wounds with skin grafts, measures that diminish local and systemic mediator releasing effects in burnt tissue, attenuating the progressive inflammatory.